Experiment on the graphical user interface (GUI) for control of remotely operated vehicle (ROV) - Chew, Kang Wei. (2009)
This report describes the development of the Hardware-In-The-Loop (HIL) simulation for Remotely Operated Vehicle (ROVII) which was developed by the Robotic Research Centre, School of Mechanical and Aerospace Engineering, NTU. The operation of the ROVII is managed by user control system through a joystick input. They are mounted on the surface vessel and with communication via R232 port. QNX 4.25 Operating System (OS) is ported in the built-in control for real-time control purpose, while Microsoft XP OS is ported on the host computer for compiling the Graphical User Interface (GUI) programming. The simulation program has been tested and coordinated with the computers to ensure the working functions of its components. To evaluate and improve the software program and interface of the ROVII, Human Interface Design (HID) principles are applied to the completed HIL simulation. Using the different principles of HID as guideline, comments and improvements are indicated for other uses. The data analysis part of the report will cover the suggested efficiency evaluation matrix and the real-time operating interface of the simulation. In conclusion of the report, improvements and recommendations are highlighted to future users for implementations and rework.